PEMBERIAN KOMPOS PADA TANAH BEKAS TAMBANG DENGAN INDIKATOR TANAMAN SAWI (BRASSICA CHINENSIS L) - Karamoy, Theffie Lientje; Kumolontang, W. J.N.; Rondonuwu, J. (EUGENIA, 2015)
ABSTRACT   This research aimed to determine the effects of compost applications on ex-mining lands by using chinese cabbage as indicator. The experiments were conducted at the Faculty of Agriculture greenhouse and the soil and compost analysis were done at the Soil Chemistry and Fertility Laboratory for a duration of two months. The research employed a Completely Randomized Design method with 5 treatments repeated 3 times to get 15 experimental units. The analysis on ex-mining soil revealed that it contained only trace amounts of soil nutrients N, P, and K. The laboratory analysis on the compost sample resulted in a C/N ratio of 11.87 which suggested that the compost was mature and ready to be used. The Analysis of Variance on research data showed that compost applications did not affect plant height between treatments at each weekly observation, and similarly did not affect leaf quantity and fresh weight at harvest time.  However, the research found that the compost applications tended to improve plant height, leaf quantity, and fresh weight of plants at harvest time.  The minimal effect of compost applications between treatments suggested that the plants did not utilized the nutrients supplied by the compost in their early stages of development.  Moreover, it was also suspected that the compost applications had not been sufficient in supplying the soil nutrients needed by the plants to ensure proper growth which ultimately affected the fresh weight of the plants at harvest time. Keywords: compost, ex-mining land